Arranjos produtivos do coco de babaçu e qualidade de vida na Região do Bico do Papagaio - TO - Santos, Lucélia Neves dos (Universidade Federal do Tocantins, 2016)
The extraction plant is the most traditional activity in the Bico do Papagaio/ TO, especially the exploitation of timber and babassu oil. The occurrence of palm Attalea spp., Synonymy Orbignya spp., Known as babassu, occupation and provides additional income for hundreds of families through its extraction. In this study, we used questionnaires and interviews to measure the index of living conditions - ICV of breakers, the collectors and artisans working in the babassu coconut activity in that region, aiming to identify models extractive babassu existing comparing them with each other, in order to analyze and identify which one (s) thereof (s) model (s) can bring a better quality of life for the communities involved. In the results and discussion of this study, it was found that among the models use babassu analyzed and compared, the project model Arts North, offers better quality of life for the artisans involved.